2022
DOI: 10.3390/ijerph20010676
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Employees’ Psychological Wellbeing: A Longitudinal Study

Abstract: Managers play a key role in realizing a humane organization of work. Transformational leadership aims to identify and examine leadership behaviors that strengthen employees’ awareness of the importance and values of task outcomes by articulating a vision for the future, providing a realistic action plan, and giving individualized support. Previous studies have revealed associations between transformational leadership and the psychological wellbeing of employees in different settings, while others did not find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…However, in a longitudinal study, Lindert, Zeike, Choi, and Pfaff (2022) found that transformational leadership did not influence psychological well-being among employees in a German company over time. Instead of the transformational leadership style, they concluded that the social environment of the company plays a greater role in employees' psychological well-being (Lindert et al, 2022). Also, they found that male employees are more likely to be affected by transformational leadership compared to female colleagues (Lindert et al, 2022).…”
Section: Relationship Between Leadership Style and Employee Psycholog...mentioning
confidence: 90%
See 2 more Smart Citations
“…However, in a longitudinal study, Lindert, Zeike, Choi, and Pfaff (2022) found that transformational leadership did not influence psychological well-being among employees in a German company over time. Instead of the transformational leadership style, they concluded that the social environment of the company plays a greater role in employees' psychological well-being (Lindert et al, 2022). Also, they found that male employees are more likely to be affected by transformational leadership compared to female colleagues (Lindert et al, 2022).…”
Section: Relationship Between Leadership Style and Employee Psycholog...mentioning
confidence: 90%
“…It was also suggested that methods including idealized influence, self-efficacy encouragement among employees, and positive relationships among employees greatly enhanced employee well-being (Kim & Cruz, 2022). However, in a longitudinal study, Lindert, Zeike, Choi, and Pfaff (2022) found that transformational leadership did not influence psychological well-being among employees in a German company over time. Instead of the transformational leadership style, they concluded that the social environment of the company plays a greater role in employees' psychological well-being (Lindert et al, 2022).…”
Section: Relationship Between Leadership Style and Employee Psycholog...mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, a supportive environment for innovation mediated transformational leadership's shortterm and long-term effects on well-being. A more recent study by (Lindert et al, 2022) in a medium-sized German company disclosed that transformational leadership did not significantly impact employees' well-being.…”
Section: The Relationship Between Transformational Leadership and Emp...mentioning
confidence: 91%
“…However, it is crucial to recognize that some studies have provided a contrary viewpoint. For instance, research by (Tafvelin et al, 2011;Lindert et al, 2022) found no direct correlation between transformational leadership and well-being. In the case of (Tafvelin et al, 2011), the positive impacts on well-being were attributed to a favorable climate for innovation rather than the leadership style itself.…”
Section: There Is a Statistically Significant Relationship Between Tr...mentioning
confidence: 99%